Concrete characteristics modelling for minimal cost and optimum performance of Abuja housing infrastructures - Ndububa, Emmanuel E.; Ijirotimi, I. O; Olowolayemo, Akeem (Open Journals Nigeria (OJN), 2022)
Abuja has experienced phenomenal infrastructural growth in the last two decades and concrete is at the heart of it. The cost of concrete has increased over the years due to the increased costs of its constituents like aggregates and cement. Many housing projects have slowed down due to the skyrocketing costs. A scientific approach in reducing concrete cost without compromising quality control is investigated. The compressive strength and workability characteristics of concrete mixes from different coarse aggregate sizes were determined in the laboratory. The cost of the mixes as determined from the market prices of the constituents were also determined. The intention was to use the Response Surface Methodology (RSM) to obtain a concrete cost predictive model that can be optimized to link the strength, workability and aggregate sizes to give a minimal cost of the concrete. Statistical packages like SPSS, WEKA and E-Views were used to verify the adequacy of the model. The results from the model show that for all concrete mixes of volume 0.041m3. The optimum cost which is the least and most reasonable cost is made from 25mm size coarse aggregate at NGN29,942.49. It also has the least slump and highest strength for each of the mix ratios of 1:3:6, 1:2:4 and 1:1½: 3 after 28 days of curing. This therefore provides the most economical option in terms of cost and quality. The integration of hardened concrete strength, wet concrete workability and aggregate sizes produced a predictive mathematical model for minimal cost, which is recommended for use in cost projection and quality control in Abuja Infrastructural development.